2004
DOI: 10.1189/jlb.1103541
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2 inhibition suppresses hemorrhage-induced priming for acute lung injury in mice

Abstract: Polymorphonuclear neutrophil (PMN) extravasation/sequestration in the lung and a dysregulated inflammatory response characterize the pathogenesis of acute lung injury (ALI). Previously, we have shown that hemorrhage (Hem) serves to prime PMN such that subsequent septic challenge [cecal ligation and puncture (CLP)] produces a pathological, inflammatory response and consequent lung injury in mice. Keratinocyte-derived chemokine (KC) and macrophage inflammatory protein-2 (MIP-2) are murine CXC chemokines found el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 37 publications
8
76
0
Order By: Relevance
“…In this regard, it is not clear whether programmed cell death plays an important role in the pathogenesis of ALI indirect (as has been suggested for ALI direct [19,22]), nor whether the pathways and cell types involved are sufficiently elucidated. In our previous studies, we have demonstrated that hemorrhage-primed neutrophils are capable of inducing ALI indirect in a septic environment, identifying them as a major contributor to the pathology of indirect ALI and supporting the neutrophil hypothesis (12,23,24). However, the upstream mechanisms that lead to the release of the major chemokines attracting these primed neutrophils, and potentially other leukocytes, as well as the cellular source of these chemotactic mediators, are unclear.…”
Section: At a Glance Commentary Scientific Knowledge On The Subjectmentioning
confidence: 55%
See 1 more Smart Citation
“…In this regard, it is not clear whether programmed cell death plays an important role in the pathogenesis of ALI indirect (as has been suggested for ALI direct [19,22]), nor whether the pathways and cell types involved are sufficiently elucidated. In our previous studies, we have demonstrated that hemorrhage-primed neutrophils are capable of inducing ALI indirect in a septic environment, identifying them as a major contributor to the pathology of indirect ALI and supporting the neutrophil hypothesis (12,23,24). However, the upstream mechanisms that lead to the release of the major chemokines attracting these primed neutrophils, and potentially other leukocytes, as well as the cellular source of these chemotactic mediators, are unclear.…”
Section: At a Glance Commentary Scientific Knowledge On The Subjectmentioning
confidence: 55%
“…Indirect ALI (ALI indirect ) was induced as described previously (12,24,33,34) by hemorrhagic shock (HEM) followed by cecal ligation and puncture (CLP) 24 hours thereafter. Importantly, while we show only the sham group as our control (which we have not found to differ from HEM or CLP alone) for the studies here, we have previously documented that neither HEM nor CLP alone is capable of inducing substantial/consistent increases in indices of lung inflammation, apoptosis, or injury (12,24,33,34).…”
Section: Indirect Alimentioning
confidence: 99%
“…The systemic inflammatory response causes tissue damage in the lung, which is the most insidious component in sepsis due to compromised gas exchange [4,21]. Convincing evidence has demonstrated that neutrophil recruitment is a critical component in the pathophysiology of septic lung injury [22][23]. However, the details of the recruitment process of leukocytes in the lung has been much less studied and seems to be more complex than that in peripheral organs.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first case-control association study using CXCL2 as a candidate gene for sepsis susceptibility, although its key role in promoting inflammatory stress has been extensively studied in different models of the disease, [7][8][9][10][11][12] and has been listed as a candidate gene for susceptibility to lung injury occurring within the setting of critical illnesses. 3 The common disease-common variant hypothesis 27 proposes that most of the genetic risk for complex diseases is owing to common variants of the loci involved.…”
Section: Discussionmentioning
confidence: 99%
“…In a septic model, Walley et al 7 found that increased expression of CXCL2 was associated with the severity of sepsis, and that antibody blocking of CXCL2 activity decreased mortality. 8,9 Congruent with these results, different studies have shown that the attenuation of CXCL2 activity, by attenuating its expression by means of glucocorticoids 6 or by siRNA gene silencing, 10 by using inhibitors of its receptor 11 or using a model of CD8 þ T/NK cell-deficient mice in which the expression of CXCL2 is decreased, 12 leads to a reduction in inflammatory response and injury.…”
Section: Introductionmentioning
confidence: 92%